2010
DOI: 10.1111/j.1365-2605.2010.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

A shorter interval between irradiation of recipient testis and germ cell transplantation is detrimental to recovery of fertility in rams

Abstract: The objective of the current study was to identify an optimal time period for donor cell transplantation after irradiation in sheep. The testes of recipient rams were treated with a single dose of 15 Gray (Gy) irradiation followed by germ cell transplantation either 3 or 6 weeks later. Transplantation of donor cells at 6 weeks after irradiation resulted in production of donor sperm by all five recipient rams compared with 4 of 11 rams transplanted at 3 weeks. Rams transplanted 3 weeks post-irradiation appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…From this comparison, we conclude that the level of donor engraftment in these two studies was similar, in spite of differences in preconditioning of the recipient tissue or isolation and manipulation of the donor cells. Similar studies with other large animals have yielded variable levels of donor sperm production (Honaramooz et al 2003, Izadyar et al 2003, Herrid et al 2009, Herrid et al 2011, Jahnukainen et al 2011, Hermann et al 2012, Zeng et al 2012, Zeng et al 2013), ranging from less than 1% to as high as 30% in sheep (Herrid et al 2009). …”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…From this comparison, we conclude that the level of donor engraftment in these two studies was similar, in spite of differences in preconditioning of the recipient tissue or isolation and manipulation of the donor cells. Similar studies with other large animals have yielded variable levels of donor sperm production (Honaramooz et al 2003, Izadyar et al 2003, Herrid et al 2009, Herrid et al 2011, Jahnukainen et al 2011, Hermann et al 2012, Zeng et al 2012, Zeng et al 2013), ranging from less than 1% to as high as 30% in sheep (Herrid et al 2009). …”
Section: Discussionsupporting
confidence: 56%
“…The development of SSC transplantation in rodents, as an alternative to embryo-mediated gene transfer, opened a new opportunity to explore this relatively less invasive, more efficient and lower cost approach in canines and other larger animal models. Successful SSC transplantations in several large animals (Izadyar et al 2003, Kim et al 2008, Herrid et al 2011, Jahnukainen et al 2011, Hermann et al 2012, Zeng et al 2012), led us believe this approach could be applied to the dog model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testicular cells are known to be able to recover from irradiation damage; goat testis treated with fractionated irradiation (2 Gy × 3 days) exhibited recovery of spermatogenesis in 60% of tubules at 6 months post-irradiation (Honaramooz et al, 2005). Based on the recovery status of spermatogenesis, most studies have performed testis germ cell transplantation between 1 and 2 months post-irradiation (Kim et al, 2006;Creemers et al, 2002), and our own study revealed the optimal donor cell transfer time for irradiated sheep testis was 6 weeks after irradiation (Herrid et al, 2011).…”
Section: Introductionmentioning
confidence: 92%